Numerical simulation of the denitrification process in the sintering flue gas SCR reactor and optimization of the ammonia injection process - Huang Dewei; Yin Xiaochun; Ding Huaiping (E3S Web of Conferences)
Iron ore sintering is an important process in ironmaking. To reduce the emissions of harmful gases such as nitrogen oxides during the sintering process, the SCR(Selective Catalytic Reduction) denitration technology can be adopted to remove nitrogen oxides and others. Based on the problem of low denitration efficiency of the SCR reactor in a certain steel plant, the Fluent software was used to numerically simulate the flow field and the denitration reaction process of the SCR reactor, and to analyze the reasons for the low denitration efficiency of the SCR reactor. According to the results of numerical analysis, the ammonia injection process was optimized. Through the finite element modeling of the optimized design scheme, the mixing degree of ammonia and nitrogen oxides and the denitration efficiency were re-analyzed. The analysis results show that the optimized design scheme effectively improves the uniformity of the ammonia-nitrogen concentration ratio above the first layer of catalysts. The original denitration efficiency of 55% is increased to 83%, which meets the requirements of the emission standards.